Readmission with venous thromboembolism after surgical treatment by primary cancer site. (December 2020) - Jarvis, Casey A.; Bonney, Phillip A.; Ding, Li; Tang, Austin M.; Giannotta, Steven L.; Kim, Anthony W.; Mack, William J.; Attenello, Frank J.
Abstract: Background: Venous thromboembolism (VTE) is a common, high-mortality condition among surgical cancer patients. Comprehensive analyses of VTE among postoperative cancer patients are lacking. We sought to determine the association between readmission with VTE and primary cancer diagnosis in a nationwide database at 90- and 180-days after initial admission for cancer surgery. Methods: Retrospective analyses of post-surgical cancer patients readmitted with VTE were conducted using data from the Nationwide Readmissions Database (NRD) (2010–2014). Multivariate logistic regression models adjusting for patient and hospital factors were used to determine 90- and 180-day readmission rates for VTE by cancer type. Patient factors associated with readmission were also examined. Results: Among a sample of 535, 992 cancer patients undergoing tumor resection, readmission with VTE occurred in 1.7% within 90-days and 2.3% within 180-days. Patients readmitted for VTE experienced a 7% mortality rate. Highest rates of VTE readmission at 180 days occurred in brain (6.7%), pancreatic (5.6%), and respiratory and intrathoracic cancers (4.4%). Using pancreatic cancer as reference, brain cancer had the highest odds of readmission at 180-days (OR 2.23, 95% CI [1.95–2.55]). Conclusion: Readmission with VTE among surgical cancer patients occurred in 2.3% of patients within 180 days. Among cancer types, primary brain cancer was independently associated with readmission with VTE. Highlights: Readmission with a VTE is a common occurrence among surgical cancer patients. Many VTE continue occur up to 180 days after initial admission. Brain tumors confer highest odds of readmission with VTE after major cancer surgery.